Biochemistry of Zinc in Antioxidant Enzymes: Implications for Veterinary Medicine: A Review - Rebat, Salam Ketab (American Journal of Biomedicine and Pharmacy, 2025)
Zinc is an essential trace element with powerful biological effects, performing vital biochemical functions associated with the antioxidant system. Zinc is a cofactor and coenzyme for the enzyme Cu/Zn-superoxide dismutase and a regulator of metallothioneins. Zinc is essential for balancing redox reactions in most processes, protecting and stabilizing biomolecules from oxidative damage. In veterinary practice, zinc is important for ensuring overall health, reproduction, immunity, and production in animals. A deficiency of this nutrient is associated with poor growth, reproductive failure, and susceptibility to infection. Its supplementation enhances its antioxidant capacity, improves reproductive performance, and enhances resilience to environmental stressors and climate change. Recent advances identify organic, inorganic, and nanoscale sources of zinc that can beneficially and significantly increase bioavailability and improve overall efficiency. However, there is still a lack of accurate knowledge and information about the prolonged toxicity of this important element, its mineral antagonisms, and requirements across species. The importance of zinc in enhancing nutritional status and overall health in animals is reflected in particular through its biochemically potent oxidizing and reducing properties. This review aims to summarize our current understanding and provide precise guidance for the next steps in animal nutrition and health research.